2013
DOI: 10.4110/in.2013.13.4.123
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Down-regulates TNF-α Secretion via Suppression of Scavenger Receptors in Macrophages

Abstract: Obesity is consistently increasing in prevalence and can trigger insulin resistance and type 2 diabetes. Many lines of evidence have shown that macrophages play a major role in inflammation associated with obesity. This study was conducted to determine metformin, a widely prescribed drug for type 2 diabetes, would regulate inflammation through down-regulation of scavenger receptors in macrophages from obesity-induced type 2 diabetes. RAW 264.7 cells and peritoneal macrophages were stimulated with LPS to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 54 publications
10
79
1
5
Order By: Relevance
“…The cell source of IL-4 is T cell, which might react differently to metformin from MNCs where IL-6 and TNF-a are derived from mcarophage. 24,25 Several randomized clinical studies have confirmed the benefits of metformin treatment, 6,8 including cardiovascular protection, lipid control, nonalcoholic simple fatty liver alleviation, and tumor inhibition. (E and F) The protein level of p65, acetyl-p65, and SIRT1 in MNCs of baseline (0 wk) after treatment for 12 weeks (12 wk).…”
Section: Discussionmentioning
confidence: 96%
“…The cell source of IL-4 is T cell, which might react differently to metformin from MNCs where IL-6 and TNF-a are derived from mcarophage. 24,25 Several randomized clinical studies have confirmed the benefits of metformin treatment, 6,8 including cardiovascular protection, lipid control, nonalcoholic simple fatty liver alleviation, and tumor inhibition. (E and F) The protein level of p65, acetyl-p65, and SIRT1 in MNCs of baseline (0 wk) after treatment for 12 weeks (12 wk).…”
Section: Discussionmentioning
confidence: 96%
“…Metformin reduced expression of pro-inflammatory and profibrotic genes in a mouse model of non-alcoholic hepatic steatosis (Kita et al, 2012), and reduced inflammation in the airways of asthmatic mice (Park et al, 2012). The anti-inflammatory effect of metformin could be due to inhibition of the NF-κB pathway, as evidenced in cultured cancer cells (Hirsch et al, 2013), vascular cells (Isoda et al, 2006), monocytes (Arai et al, 2010) and macrophages (Hyun et al, 2013). The anti-fibrotic effect of metformin has been characterized mostly in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 97%
“…Recent trials of anti-inflammatory drugs and remedies have concentrated on blocking the production of inflammatory gene products by suppressing the transcriptional activation of inflammatory genes (Ayele et al, 2013;Kim et al, 2013). For instance, targeting the signalling cascade that activates nuclear factor (NF)-κB and activator protein (AP)-1 has been shown to effectively inhibit the release of NO, PGE 2 , TNF-α, interleukin (IL)-1, MCP-1, and certain hydrolytic enzymes (Eo et al, 2013;Hyun et al, 2013). Much research has focused on identifying candidate materials that are safe and that can prevent inflammation-based diseases by inhibiting upstream signalling events involved in inflammatory gene expression.…”
Section: Introductionmentioning
confidence: 99%